Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1080/10615806.2015.1025764
|View full text |Cite
|
Sign up to set email alerts
|

Work-related stress and cognitive enhancement among university teachers

Abstract: The results increase our knowledge about the prevalence of CE-drug use and our understanding of what motivates and inhibits the use of CE-drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
96
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(109 citation statements)
references
References 70 publications
7
96
1
5
Order By: Relevance
“…In the case of Germany, life time prevalence use of methylphenidate and amphetamines for cognitive enhancement purposes in pupils was 1.55 % and in students 0.78 %, with last year and last month prevalence rates being significantly lower [61]. Another three studies of German university teachers also showed a very low prevalence rate for the use of these drugs [62]. In the case of university students in the UK and Ireland, a majority of those surveyed were unaware and/or uninterested in putative PCEs [8].…”
Section: Presumption #4: There Is Evidence That Pce Is Increasingly Imentioning
confidence: 86%
See 2 more Smart Citations
“…In the case of Germany, life time prevalence use of methylphenidate and amphetamines for cognitive enhancement purposes in pupils was 1.55 % and in students 0.78 %, with last year and last month prevalence rates being significantly lower [61]. Another three studies of German university teachers also showed a very low prevalence rate for the use of these drugs [62]. In the case of university students in the UK and Ireland, a majority of those surveyed were unaware and/or uninterested in putative PCEs [8].…”
Section: Presumption #4: There Is Evidence That Pce Is Increasingly Imentioning
confidence: 86%
“…For instance, recent surveys have analyzed the various drivers behind individuals' willingness to use putative PCEs and have identified several factors that increased that willingness [62,76]. Amongst those were greater inclinations to use PCE when their enhancing effect was expected to be powerful, when more of one's peers used them, and when one suffers from academic procrastination.…”
Section: A Positive Shiftmentioning
confidence: 97%
See 1 more Smart Citation
“…For commentators, particularly in disciplines such as neuroethics, the growth of the PCE legend has offered an argument for the important role of discussions about the politics of enhancement; attending to legality and decriminalization, workplace pressure, education, and neoliberalism. (Sampson, 2016;Wiegel, Sattler, Göritz, & Diewald, 2016). The dialogue, for better or worse, is one that moves between academic disciplines and the popular press where commentators attempt to open, and perhaps feed, the debate.…”
Section: The Self-referential Debate About Neuro-enhancement Technolomentioning
confidence: 99%
“…The intensity and sources of strain related to teachers' work are a topic of growing interest in different educational settings (Kosir, Tement, Licardo, & Habe, 2015), showing that workers in the education sector are a high-risk population with a strong prevalence of work-related stress (Wiegel, Sattler, Göritz, & Diewald, 2015).…”
Section: Introductionmentioning
confidence: 99%